Peran Orang Tua Dalam Penanganan Anak Korban Bullying - Agustini, Dewi; Nuriana, Mutia Azizah; Nadiroh, Nadiroh; Ridho, Muhammad Rosyid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This research aims to analyze the role of parents in handling children who are victims of bullying. This type of research is qualitative in nature, utilizing data sources from the literature. Bullying poses a significant threat to children's well-being, manifesting in various forms including physical, verbal, psychological, social, and cyber dimensions. This study examines the nuanced facets of bullying, encompassing definitions, typologies, and repercussions, with a particular emphasis on the pivotal role of parental involvement in alleviating its adverse effects. Drawing from psychological insights, it delineates the profound psychological, social, academic, and physical ramifications of bullying on victims, highlighting the imperative for targeted interventions. Parental engagement emerges as pivotal in fostering resilience and facilitating recovery, through strategies encompassing open dialogue and the cultivation of social competencies. Additionally, the exploration extends to diverse parenting styles and their implications in addressing bullying incidents. Therapeutic interventions, including individual, family, and group therapies, religious guidance, alongside cognitive-behavioral and remedial approaches, are discussed, with a focus on indicators of successful counseling such as reduced anxiety and enhanced coping mechanisms. Advocating for a holistic approach involving educators, parents, and mental health professionals, and religious guidance. The study underscores the imperative of creating a nurturing environment, empowering children to report incidents, and engaging parents in the counseling process to mitigate the pervasive impact of bullying on children's well-being.